Innovación en MIPYMES mediante la implementación de la metodología de innovación abierta, talleres empresariales de innovación y creatividad aplicada “TEICA” - Tuberquia Vanegas, Elizabeth
Innovation is an alternative to which many companies turn to position themselves on the market and survive the permanent doses of globalization that tend to overshadow their management, products and services with the constant and innovative launch of competition in the different fields of production. Nevertheless, being a wheel that revolves around new opportunities, the small and medium companies die early in their impotence to compete with the giants of the industry. They do not do it because they do not know their market, they do it because there is a widespread fear to innovate, fear based on ignorance, lack of opening to new ideas, inability to invest or fear to lose their efforts or lack of vision, initiative and creativity of those who make them up. This study was carried out to understand the degree of opening to innovation the companies that sponsor the trainees of the Center of Administrative Management have by applying two online instruments to both entrepreneurs and collaborators and based on their results offer academic and administrative management alternatives to favor innovativeprocesses in organizations.